Quadri di una rigenerazione. Ecologie dell’ambiente urbano e antropologia applicata ai territori a Milano - Grassi, Paolo (Antropologia Pubblica, 2025)
Like many other cities, Milan’s urban ecology is characterised today by the presence of vast spaces that are apparently “empty” or in need of renovation, objects of regeneration interventions, either in progress or merely planned. They are often interstitial spaces, because they are “abandoned”, under-utilised, re-naturalised, or considered obsolete, effigies of the past and stratified. They are, however, anything but “marginal” spaces. Stadiums, racetracks, former industrial areas, railway yards and military areas, on the contrary, provide insight into the future of the city, its policies, and its development dynamics. Urban regeneration is therefore a field full of meanings, a prism through which to observe transformative processes. This observation poses two challenges to anthropological research. The first has to do with the multi-scalarity of the object in question and makes explicit a cognitive instance: how is it possible to investigate the anthropological dimensions inherent to urban macro-processes from an ethnographic approach? The second relates instead to the theme of representation and refers to the choice of an authorial strategy: how to account, through the written text, for this multiscalarity? I will try to answer these questions by relating some field notes collected in different places and times in Milan between 2022 and 2023. In conclusion, moving to a more applied level, I will reflect on the social use that this type of analysis can offer, beyond its critical and deconstructive power.